Ovarian histology and reproductive cycle of Columbina picui (Temminck,1813) (Aves: Columbidae) from Córdoba, Argentina - Altamirano, Elsa Inés (2009)
The annual reproductive cycle of Columbina picui was studied and characterized by a structural and quantitative analysis of the ovary. Adult females were collected in Sierra de Macha (Totoral, Córdoba, Argentina) between the years 2005—2006. During the phase of recrudesence gonadal (June to March), three values maximum were determined, the first one was observed in June as a result of the first oviposition of the subadults (individual with external adult characteristics but vestigial Bursa of Fabricius presence), the remaining values were registered one in September and the other one in January, corresponding that of the mature females. The ovaric regression is initiated with the hatching, and the resting stage between April and May, in the most of the birds. Two types of atresia were identified: a) the non bursting type, with no rupture of the follicular wall, which includes lipoidal (primordial follicles) and lipoglandular atresia, (previtelogenic follicles and small vitelogenic follicle), of them were observed during the whole reproductive cycle ; and b) the bursting atresia, with rupture of the follicular wall (vitelogenic follicles > 800 μm) only was observed during the gonadal regression. The abundance of females with capacity of reproducing during most of the year and the extensive phase of gonadal recrudescence were characteristics of the C. picui reproductive cycle.